ANALYSIS OF SOLVENCY RATIO AND ACTIVITY RATIO IN THE FINANCIAL PERFORMANCE OF PT BUKIT ASAM TBK - Zagita, Tara; Novalia, Nurkardina; Suhada, Suhada (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2024)
This study aims to determine how the financial performance of PT Bukit Asam Persero Tbk in this case is measured based on the analysis of solvency ratios and activity ratios. The population of this study is the financial statements of PT Bukit Asam Persero Tbk, where the sample of this study is the balance sheet and income statement for 4 years for the period 2020-2023. The method used is qualitative, and the data collection techniques in this study use documents and library research. Meanwhile, data analysis techniques in the study were analyzed through the calculation of solvency and activity ratios. The results of this study indicate that the financial performance of PT Bukit Asam Persero Tbk analyzed using solvency ratios based on the debt to assets ratio shows that in 2020-2021 it is in good condition, while in 2022-2023 it is not good. Based on the debt to equity ratio, it shows that in 2020-2023, although the ratio continues to increase, it is still considered in good condition, and the long term debt to equity ratio shows that the financial performance in 2020-2023 is not good. The results of research using activity ratios based on inventory turnover show that financial performance in 2020-2021 is good, while in 2022-2023 it is not good. Based on fixed assets turnover, it shows that in 2020, 2021, and 2023 it is not good, while in 2022 it is good.